(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
The present study is aimed at determining the levels of toxic heavy metals (Cadmium, Chromium, Lead and Zinc) and mineral elements (Potassium, Sodium, Magnesium and Calcium) in parts of spinach and cabbage collected at Kofar Marusa, Kofar Durbi and Kofar Sauri irrigation areas located along Ginzo River, Katsina, Katsina State, Nigeria. A total of 40 samples were analysed for the presence of toxic heavy metals and mineral elements using Atomic Absorption Spectrophotometry. Concentration of chromium, lead and zinc in leaves of cabbage we found to be within the permissible limits except cadmium (0.40ppm and 0.39ppm) that exceeded the 0.2ppm WHO/FAO, 1984 permissible limit in leaves of Kofar Marusa and Kofar Durbi samples. In roots of cabbage, cadmium level exceeded the standard. Concentration of elements in head of cabbage is within the permissible, except cadmium in all samples. In leaves, stems and roots of spinach, cadmium showed exceeded level and have highest values of 0.50±0.01ppm, 0.59±0.0ppm and 069±0.01ppm all obtained in Kofar Marusa samples. The findings showed that Ginzo River is suitable for agricultural purpose. Level of cadmium in soil, water, roots, stems and leaves have exceeded the permissible limit while concentration of chromium, lead and zinc in all samples is similar with set standards.